Building a Smart Gardening System and Plant Monitoring Using IoT - Mohd Zaki, Ain Zulaikha; Yakub, Fitri; Fakharulrazi, Alyani Nadhiya; Azizan, Azizul; Harun, Aizul Nahar; Abdul Rahim, Zulhasni (Journal of Sustainable Natural Resources, 2021)
Gardening activities usually required a lot of time and gardeners may face varieties of problems such as sticking to the designated watering schedule. Thus, this paper intends to solve these problems by introducing the Smart Gardening System. By using this system, users will be able to control and monitor the watering schedule and the sufficiency of lights while ensuring that the plants are taken care of accordingly. The smart gardening system is different from the normal gardening products that are already available in the market because of the implementation of Internet of Things (IoT) in the system to facilitate the work for its users. By using this home-based system, users can set the watering and lighting schedule automatically by using the designated application via smartphone. Besides, users will also be notified on the moisture level of soil, light-exposure, and the water level in water tank through the application. This will allow the users to monitor the watering system and only come to refill it when the water tank is empty. This system is an advantage as it can run automatically. From this research, the benefit of smart gardening system is proven via the execution of IoT which requires less human intervention for the system to operate. Moreover, the sensors are used to gather and update all the data that is convenience to the user to keep updated on the parameter and information about the plant in a real time without physical present.